An Analysis of Diversity of the GS-14, GS-15, and SES Ranks in the Department of Veterans Affairs from 2002-2022 - Malone, Duvalier (Advances in Social Sciences Research Journal, 2023)
This article examines the diverse types of diversity, including age, disability, and sex/gender diversities, among the top three levels of management at the Department of Veterans Affairs. This research will shed light on these differences and their implications. By examining the differences among the top three levels of the senior leadership branch of government at the Department of Veterans Affairs (VA), this research seeks better to understand the impact of changes in diversity policies. As the Department of Veteran Affairs continues to transform, it is increasingly vital that we have the tools necessary to measure the impact of our efforts on our changing culture. From a diversity point of view, it will help us understand veterans as a social group and their inclusion in the workplace. In contrast, the person-environment fit perspective helps us describe veterans’ compatibility with their work environments in terms of organizational demands and veterans’ needs. National attention and resources are being brought to the issue of supporting the economic success of Veteran’s Affairs.